PERANCANGAN MEDIA PEMBELAJARAN FIKIH BERBASIS AUGMENTED REALITY DI MTsN 06 AGAM - Resnawita; Sarwo Derta; Liza Efriyanti; Supriadi (KOLONI, 2022)
This study aims to make it easier for teachers to carry out fiqh lessons for class VII at MTsN 06 Agam. The research method used is the development (Research and Development). By using the Luther Sutopo version of the development model which consists of 6 stages, namely Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The product test used in this study is a test of validity, practicality and effectiveness. Based on the results of the research that has been done, it can be concluded that the resulting application can be utilized and feasible. So the learning media on Augmented Reality-based fiqh subjects that the author has designed has been said to be practical and helpful in the teaching and learning process. Keywords: Based Learning, Fiqh, Augmented Reality